Durability of Pulmonary Vein Isolation with Cryoballoon Ablation: Results from the Sustained PV Isolation with Arctic Front Advance (SUPIR) Study - Reddy, Vivek Y; Sediva, Lucie; Petru, Jan; Skoda, Jan; Chovanec, Milan; Chitovova, Zita; Di Stefano, Paola; Rubin, Ethel; Dukkipati, Srinivas; Neuzil, Petr (Journal of cardiovascular electrophysiology, 2015)
INTRODUCTION: Pulmonary vein (PV) reconnection remains the most important cause of AF recurrence after AF ablation. The second-generation cryoballoon catheter's ability to achieve durable PV isolation was assessed in a prospective nonrandomized clinical trial. METHODS AND RESULTS: PV isolation was performed by 4-minute ablations. Following verification of electrical isolation by a multielectrode mapping catheter, 1 additional lesion per PV was applied. Esophageal temperatures were monitored and all patients underwent postprocedure esophageal endoscopy. All patients underwent a second PV remapping procedure at ∼3 months to assess for PVI durability. Eighty-four (100%) veins were acutely isolated using only the 28 mm cryoballoon in 21 consecutive PAF patients with 2.2 ± 0.6 cryoapplications per vein, with the majority (83%) occurring after a single freeze. One patient presented with hematemesis and an esophageal ulceration that was treated conservatively; there were no episodes of esophageal fistula or phrenic nerve palsy. At 3.4 (2.9-4.1) months postablation, 68/75 veins (91%) remained electrically isolated; all PVs remained durably isolated in 79% of patients. Two patients accounted for 5 of 7 reconducting veins. The most common site for reconnection was the inferior aspect of the RIPV (3/7 reconnections). Reconnected veins had poorer occlusion at the index ablation procedure than veins that maintained chronic isolation (occlusion grade 2.9 ± 0.7 vs. 3.4 ± 0.7, P = 0.001). Clinical AF recurrence was detected in 2 patients (11%) at follow-up. CONCLUSIONS: The improved thermodynamic characteristics of the second-generation cryoballoon led to a high rate of both single-shot PVI and chronic lesion durability. This high rate of durable PV isolation is anticipated to translate to improved clinical outcome.
Keywords: nerandomizované kontrolované studie jako téma; Equipment Design; srdeční katétry; Recurrence; Female; Electrophysiologic Techniques, Cardiac; Atrial Fibrillation; elektrofyziologické techniky kardiologické; Pulmonary Veins; výsledek terapie; ženské pohlaví; Action Potentials; Time Factors; časové faktory; lidé; recidiva; Treatment Outcome; venae pulmonales; Non-Randomized Controlled Trials as Topic; Esophagoscopy; prospektivní studie; Male; Aged; Prospective Studies; Czech Republic; Česká republika; fibrilace síní; lidé středního věku; senioři; kryochirurgie; mužské pohlaví; Cardiac Catheters; design vybavení; Cryosurgery; ezofágoskopie; Middle Aged; akční potenciály; Humans